2009
DOI: 10.1037/a0016426
|View full text |Cite
|
Sign up to set email alerts
|

A process analysis of the transmission of distress from interparental conflict to parenting: Adult relationship security as an explanatory mechanism.

Abstract: Towards advancing conceptualizations of the spillover hypothesis, this study examined the conditions and mechanisms underlying the transmission of distress from the interparental relationship to parenting difficulties over a two year period in a sample of 233 mothers (M = 35.0 years) and fathers (M = 36.8 years) of kindergarten children. Findings from autoregressive structural equation models indicated that parent gender moderated associations between interparental conflict and parental psychological control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
122
6
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 90 publications
18
122
6
1
Order By: Relevance
“…Our results were consistent with earlier work (e.g., Davies et al, 2009), in showing that marital functioning was related to fathers' responsiveness (but not mothers'; see Stroud et al, 2011, for a discussion of this finding), but mothers' responsiveness (but not fathers') was related to child adjustment. This suggests that although mothers may be able to contain emotions and insecurities generated in the marriage (e.g., Davies et al, 2009), when their parenting is compromised by other factors (e.g., Nelson et al, 2009), child adjustment may be more strongly linked to mothers' responsiveness. This finding adds to a mixed literature regarding the relative influence of mothers' versus fathers' parenting.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results were consistent with earlier work (e.g., Davies et al, 2009), in showing that marital functioning was related to fathers' responsiveness (but not mothers'; see Stroud et al, 2011, for a discussion of this finding), but mothers' responsiveness (but not fathers') was related to child adjustment. This suggests that although mothers may be able to contain emotions and insecurities generated in the marriage (e.g., Davies et al, 2009), when their parenting is compromised by other factors (e.g., Nelson et al, 2009), child adjustment may be more strongly linked to mothers' responsiveness. This finding adds to a mixed literature regarding the relative influence of mothers' versus fathers' parenting.…”
Section: Discussionsupporting
confidence: 92%
“…However, to establish an intervening mechanism, direct paths between the predictor and outcome variables need not be significant (MacKinnon et al, 2002). That is, even if marital functioning is not directly related to children's level of adjustment, marital functioning may be indirectly related to child adjustment via parenting (e.g., Davies et al, 2009). Thus, to examine whether parenting may serve as a mediating or an intervening variable, we estimated the magnitude of the direct paths between marital functioning and children's adjustment by constraining the indirect paths to zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marital dissatisfaction, in contrast, may lead to mothers feeling more stressed by their childcare responsibilities (Goldberg & Easterbrooks, 1984), which may increase the possibility that the stressed mothers would use harsh discipline with their children. This finding suggested that unlike in American contexts where fathering may be more influenced by their marital relationship (Coiro & Emery, 1998;Cummings et al, 2010;Davies et al, 2009;Stroud et al, 2011), in Chinese contexts, mothering may be more likely determined by the state of the marital relationship than fathering. That is, although there is some research with Western samples supporting fathering-vulnerability hypothesis (Cummings et al, 2010;Davies et al, 2009;Stroud et al, 2011), the present research provided at least some support for the mothering-vulnerability hypothesis in Chinese societies.…”
Section: Discussionmentioning
confidence: 78%
“…According to this perspective, the associations between marital satisfaction and harsh discipline may be different for mothers and fathers. Indeed, in the few studies that investigated the spillover effects between marital relationship and parent-child relationship, it was found that negative marital relations had stronger effects on father-child relationships than on mother-child relationships, supporting fathering-vulnerability hypothesis (Cummings, Merrilees, & George, 2010;Davies, Sturge-Apple, Woitach, & Cummings, 2009;Stroud, Durbin, Wilson, & Mendelson, 2011). Given the theoretical hypothesis and empirical findings, it is possible that unsatisfying marital relationship may be more likely to lead the fathers who experienced parenting stress to use harsh discipline compared to the mothers with similar experiences.…”
Section: Parent Gender Differences In the Moderating Mechanismmentioning
confidence: 89%